Lower Extremity Nerve Injury in Childbirth. Issue 3 (May 2021) - Wisner, Kirsten
Abstract : During the childbirth process women are at risk for lower extremity nerve injury. Our maternity nursing expert, Dr. Wisner, reviews the recent practice brief on this topic by the Association of Women's Health, Obstetric, and Neonatal Nurses.